Single or multiple arterial grafting to design a coronary bypass: a retrospective study - A. V. Frolov; N. I. Zagorodnikov; R. S. Tarasov; E. V. Grigoriev (Фундаментальная и клиническая медицина, 2023)
Aim. To compare the efficiency of single arterial grafting (SAG) and multiple arterial grafting (MAG) at coronary artery bypass graft (CABG) surgery in the long term.Material and Methods. To assess the angiographic outcomes, we evaluated the patency of 323 bypasses at 102 angiograms obtained during coronary angiography performed > 10 years post-CABG surgery.Results. Out of 323 analyzed bypasses, 230 (71.2%) showed physiological functioning, whereas stenosis, occlusions, and other coronary artery alterations were found in 93 (28.8%) bypasses. The most common cause for the failure of anastomoses was competitive flow (most frequently registered in the anastomoses between left internal thoracic artery and left anterior descending artery, left internal thoracic artery and diagonal branches of left anterior descending artery, right internal thoracic artery and left anterior descending artery, and between right internal thoracic artery and right coronary artery), poor distal bed (most frequently revealed in the anastomosis between left internal thoracic artery and obtuse marginal artery, saphenous vein and diagonal branches of left anterior descending artery, saphenous vein and obtuse marginal artery, and between saphenous vein and right coronary artery), progression of atherosclerosis in combination with poor distal bed (most frequently detected in the anastomosis between right internal thoracic artery and obtuse marginal artery), and combination of poor distal bed, competitive flow, and graft degeneration (most frequently found in the anastomoses between radial artery and obtuse marginal artery and between radial artery and right coronary artery). In 5 (5.4%) cases, the cause of coronary bypass dysfunction was unclear.Conclusion. The main causes for the coronary bypass failure included competitive flow (in case with multiple arterial grafting) and poor distal bed (in case with single arterial grafting).